Natural and Synthetic Sialylated Glycan Microarrays and Their Applications - McQuillan, Alyssa M.; Byrd-Leotis, Lauren; Heimburg-Molinaro, Jamie; Cummings, Richard D. (Frontiers in Molecular Biosciences, 2019)
This focused chapter serves as a short survey of glycan microarrays that are available with sialylated glycans, including both defined and shotgun arrays, their generation, and their utility in studying differential binding interactions to sialylated compounds, highlighting N-glycolyl (Gc) modified sialylated compounds. A brief discussion of binding interactions by lectins, antibodies, and viruses, and their relevance that have been observed with sialylated glycan microarrays is presented, as well as a discussion of cross-comparisons of array platforms and efforts to centralize and standardize the glycan microarray data.